Pixel programming aspects of digital image - Birškytė, Rima (Lietuvos matematikos rinkinys, 2012)
This article describes a realization of the mathematics and informatics subjects by using visual objective programming facilities. For solving advanced computer graphics tasks, seems comfortable to use new estimated mathematics programs and packages, which already are enriched with digital image processing tools, allowing to create, paint and animate a various objects of the real world on computer screen, to extend the products of virtual reality. The described image reconstruction algorithms have been evaluated on the basis of computer simulations.